Áhir budhníyaḥ and bhūmidundubhiḥ: The serpent of the deep and the earth-drum. A hypothesis of etymological and/or cultural connections - Rossi, Paola Maria (Lingua Posnaniensis, 2019)
Such a cultural transformation, carried out in the Middle and Late Vedic period in northern India, entailed that ancient Indo-European tribal cultural traits were intermingled with cultural substrate/adstrate elements: the term dundubhí is “etymologically” connected to the Proto-Muṇ ḍa *ḍub-/*dum- “to be swollen, roundish”, the PAA *duby-/*dub- “tail, buttock, animal limbs”, and Middle Iranian isoglosses meaning “tail, extremities, fat-tailed animals”. Moreover, as bhūmidundubhi “earth-drum” beaten on the border of the ritual area in the mahāvrata rite, representing earthly sonority and the “mighty bellowing” of cattle, it is associated with the IIr myth of valá/vará, the “enclosure”, in which the treasure/cattle “endowed with rock as foundation” (ádri-budhna, ṚV 10.108.7ab), is hidden. The related lexicon and imagery recall mythical archetypes, such as the Serpent of the Bottom (OIA áhir budhníyaḥ, Gr Pythô ophis) or primordial Monster of the Deep (Gr Typhôn/Typhôeus), and BMAC interferences are also embedded. However, although linguistic evidence confirms the etymological relationship between the OIA budh-ná and the Greek pythmên, the case of the Greek Typhôn/Typhôeus seems more uncertain: the IE reconstruction *dhubh-/*dhub “depths” is considered a secondary outcome, and cannot be convincingly applied to the term dundubhí, because of its onomatopoeic nature. Nonetheless, as an outcome of linguistic and cultural interferences, “Sanskritised” within the ritualism, which supported the paradigm of the Kuru-Pañcāla sovereignty, the term dundubhí conveys the double “redundant” value of deep/high sonority and swollen/roundish abundant prosperity, to which the figure of Bṛhaspati is correspondent: in ṚV 10.64.4 he is defined as the kaví tuvīrávān “poet endowed with powerful bellowing”, which announces prosperity, spreading it loftily, throughout the cosmos.